2011
DOI: 10.1007/s00464-011-1810-2
|View full text |Cite
|
Sign up to set email alerts
|

Pain characteristics after laparoscopic inguinal hernia repair

Abstract: Pain was most intense 3 h after the operation and declined to low levels within the first 3 days. Visceral pain was by far the dominating pain component compared with incisional and shoulder pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 14 publications
1
15
0
2
Order By: Relevance
“…After laparoscopic groin hernia repair, pain intensity peaks on day 0 [13–58 mm, range of median values in the papers, visual analogue scale (VAS), 0–100 mm] with moderate to severe pain in half of the patients and decreases during the following days . Most studies did not evaluate pre‐operative pain, but some studies found that pain intensity at day 3 was comparable to pre‐operative levels, although findings are not consistent because pain in several studies persisted until day 7 or longer . On day 7, seven patients (4%) out of 196 patients who underwent TAPP reported VAS 6–10 (VAS scale 0–10) .…”
Section: Resultsmentioning
confidence: 99%
“…After laparoscopic groin hernia repair, pain intensity peaks on day 0 [13–58 mm, range of median values in the papers, visual analogue scale (VAS), 0–100 mm] with moderate to severe pain in half of the patients and decreases during the following days . Most studies did not evaluate pre‐operative pain, but some studies found that pain intensity at day 3 was comparable to pre‐operative levels, although findings are not consistent because pain in several studies persisted until day 7 or longer . On day 7, seven patients (4%) out of 196 patients who underwent TAPP reported VAS 6–10 (VAS scale 0–10) .…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, a study by Tolver et al found that 50% of patients experience moderate to severe pain on the first post-operative day after a laparoscopic procedure although the intensity of this pain usually decreases significantly by the third post-operative day [18].…”
Section: Comparison Of Polypropylene Mesh Vs Parietex Progrip Tm Meshmentioning
confidence: 98%
“…Biomechanical properties such as weight, surface area, pore size and the structure of the mesh combined with its chemical properties, seem to influence the risk of meshrelated post-operative complications of shrinkage, migration, infection and nerve damage (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%